Os impactos da previdência social rural na agricultura familiar e no desenvolvimento territorial: o caso do 1º distrito do município de Canguçu/RS - Konzgen, Queli Rejane da Silva (2023)
Family farming usually covers production for the family's own consumption with production intended for the market. The category, in many cases, accesses public policies and one that deserves emphasis is rural social security. The present research has as its study area on the municipality of Canguçu/RS, where it is noticeable the importance of family farming and rural social security for local development. The study aims to understand the impacts of rural social security for family farmers and for the territorial development of the first district of the municipality of Canguçu/RS. The investigation consists of bibliographic and documentary research about the theme and the study area, and during this phase, parameters were developed for each of the dimensions of territorial development, in order to understand the reality. A field survey was also conducted on family farming properties located in the 1st district of the municipality of Canguçu/RS, which had at least one retiree or pensioner from rural social security. During the fieldwork, sampling in area units was used, the practice of "snowball" sampling, interviews by guidelines, non-participant observation, field diaries, photographic surveys, and verification of the geographical coordinates of the headquarters of the properties studied. In addition, structured interviews were conducted with representatives of the institutions that have a relationship with rural retirees and pensioners. Rural social security in the economic dimension is a public policy that contributes to income formation, improves production, and maintains the families studied in the rural space. This public policy also impacts the maintenance and expansion of commercial activities in the urban space of Canguçu. The right to rural benefits provides greater financial autonomy for women in the political dimension and highlights the relevance of institutions in the constant claim for the maintenance of the right to rural social security for rural workers. In the cultural dimension, the impacts are visible in the changes in eating habits. The natural/environmental dimension has negative impacts that need to be overcome not only among the elderly, but also among the rural youth, through public policies that encourage production in a more sustainable way, promoting in the future the development of the territory as a whole.